The Association Between Post-stroke Depression, Aphasia, and Physical Independence in Stroke Patients at 3-Month Follow-Up - Wang, Shuo; Wang, Chun-Xue; Zhang, Ning; Xiang, Yu-Tao; Yang, Yang; Shi, Yu-Zhi; Deng, Yi-Ming; Zhu, Mei-Fang; Liu, Fei; Yu, Ping; Ungvari, Gabor S.; Ng, Chee H. (Frontiers in Psychiatry, 2018)
Objective: Few studies have examined the association between post-stroke depression (PSD), aphasia and physical independence in Chinese patients. This study investigated the above association in stroke patients in China at 3-month follow-up. Methods: Altogether 270 patients within 14 days after ischemic stroke were recruited and followed up at 3 months. PSD, aphasia, and physical functional status were measured using the Stroke Aphasia Depression Questionnaire (SADQ), Western Aphasia Battery (WAB) and modified Rankin Scale (mRS), respectively. Patients with mRS total score >2 were considered as having ‘physical dependence’. Results: Out of 248 patients at 3-month follow up, 119 (48%) were rated as having physical dependence. Multiple logistic regression analyses revealed that female (p=0.04; OR=2.2; 95% CI: 1.0-5.1), more severe stroke at admission (p<0.01; OR=1.4; 95% CI: 1.3-1.5) and more severe PSD at 3 months (p=0.01; OR=1.05; 95% CI: 1.01-1.1) were independently associated with physical dependence at 3 months. Conclusions: Greater PSD and stroke severity were independently associated with physical dependence at 3 months after stroke. Aphasia was also associated with physical dependence but the relationship was not significant. Early and effective depression screening, treatment and stroke rehabilitation appear to be important to improve the physical outcome and reduce the burden of stroke survivors.